Group Guidance Based on Gestalt Theory to Develop Creativity in Learning - Putri, Rizki Diana (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2019)
Creativity in learning is a character that is the power of individuals to be able to complete their competence in learning. In learning, creativity makes students sensitive or aware of problems, shortages, understanding in knowledge, by gathering existing information, limiting information, or connecting (looking for) nothing, finding answers, making hypotheses, changing, and testing them.  It is accepted and finally communicates the results. The purpose of this study is to get a complete picture of the learning process and group guidance using Gestalt in developing learning creativity. The research method uses literature studies. In operational terms, creativity in learning requires students to be able to reflect the abilities that are responsible for the burden, burden, and the learning process. The understanding resulting from the reflection process becomes a reference in the formulation of the problem. The results of the literature study show that group guidance with Gestalt theory can help students develop their creativity in learning. Give advice about assistance when interacting and interpersonal problems, as well as creativity assistance, implemented to support/bring up productive solutions in efforts to improve Gestalt. Gestalt-based group tutoring to develop learning creativity gathers students to find opinions about the challenges of learning, to finally find the discovery of actions that are appropriate for yourself. Group techniques that can be used are lap exercises, fantasy exercises, and homework